Estimation of the efficiency of combining a npp with a hydrogen facility under conditions of safe use of hydrogen in a steam turbine cycle - R. Z. Aminov; A. N. Bairamov (Известия высших учебных заведений: Проблемы энергетики)
THE PURPOSE. System efficiency and competitiveness assess of a new scheme for combining a nuclear power plant with a hydrogen complex based on additional heating of feed water and superheating of live steam in front of the high-pressure cylinder of a steam turbine. METHODS. Basic laws of thermodynamics were applied when developing and substantiating a new scheme for combining a nuclear power plants (NPP) with a hydrogen facility; theoretical regularities were applied of heat engineering; basic regularity were applied of fatigue wear of power equipment and assessment of its working resourse; basic regularities were applied for the assessment of operating costs and net present value (NPV). RESULTS. A new scheme is presented of the combination of a nuclear power plant with a hydrogen facility and a description of its operating principle on the example of a two-circuit nuclear power plant with a VVER-1000 reactor and a C-1000-60 / 1500 turbine. The data are presented on an increase in the productivity of steam generators at nuclear power plants with additional heating of feed water in the range of 235-250 ° C from its nominal value of 230 ° C. The temperature was estimated of live steam superheat depending on the temperature of the additional heating of the feed water. The results are presented of the calculation of the generated peak power by the power unit and the efficiency of conversion of the night off-peak power of the NPP into peak power, as well as the efficiency of the power unit of the NPP depending on the temperature of additional heating of the feed water. Main regularities are given for taking into account the fatigue wear of the main equipment of the hydrogen facility, including the rotor of the NPP turbine in the conditions of the stress-cyclic operation. The results are presented of assessing the cost of peak electricity NPP in combination with a hydrogen facility in comparison with a pumped storage power plant (PSPP) both for the current period and for the future until 2035. CONCLUSION. Hydrogen facility efficiency and competitiveness depends significantly on the intensity of the use of the main equipment in the conditions of the intense-cyclic operation. The hydrogen facility will competitiveness noticeably increase in comparison with the PSPP in the future. Efficiency of the NPP power unit and NPV is highest when the feed water is heated to 235 ° C and superheating of live steam in front of the high-pressure cylinder of the C-1000-60/1500 turbine up to 470°C.The hydrogen facility competes with the PSPP with her specific capital investment at the level of 660 USD / kW, provided that the boosting capabilities of the turbine are used with live steam overheating at 300 ° C and additional heating of feed water to 235°C on the current period. The PSPP does not compete with the hydrogen facility both for the current period and in the future with her specific capital investment of $ 1,500 / kW and above.